Analysis of Online and Offline Travel Agents’ Contribution to Room Occupancy - Ni Kadek Masita Hardiani; Budi Susanto; I Ketut Astawa; Nyoman Mastiani Nadra; Made Sudiarta; Ni Made Sudarmini (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: The aims of this study are to know the contribution of Online Travel Agents and Offline Travel Agents to room occupancy at a hotel in Denpasar, Bali, Indonesia, and to find out the comparison of contribution from Online Travel Agents and Offline Travel Agents to room occupancy at the hotel. Research methods: Data collection methods used are observation, interview, and study documentation. The analysis technique used is quantitative analysis, qualitative analysis, and descriptive statistics from secondary data. The stages of the data analysis technique start from the classical assumption test, multiple regression analysis, hypothesis testing using SPSS 21 program, and descriptive statistical techniques. Results and discussion: The results of this study indicate that the t count value of the online travel agent contribution is greater than the t table (4.280> 1.692). Meanwhile, the t count value of the contribution of the offline travel agent also has a greater value than the t table (4,280> 1,692). Based on the data obtained, the contribution of the Online Travel Agent and Offline Travel agents from 2017 to 2019 has fluctuated every year. Implication: The contribution to the development of the Online Travel Agents has increased every year, while the contribution of Offline Travel Agents has decreased in 2019. However, the largest contribution still comes from the Offline Travel Agent. In an effort to increase room occupancy, the hotel should further expand the collaboration networking with Online Travel Agents to increase the contribution that can be generated by Online Travel Agents. Keywords: online, offline, travel agent, room occupancy.